The Use of Necessitas Non Habet Legem and Wederspanningheid in Law Enforcement for Covid-19 Vaccination in Indonesia - Moch. Marsa Taufiqurrohman; Muhammad Toriq Fahri; Robi Kurnia Wijaya; I Gede Putu Wiranata (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The majority of scientific research in the world agrees that vaccination is a vital instrument that aims to solve the problem of the Covid-19 pandemic. In achieving this goal, the government is trying to ensure that vaccinations run as they should. Even though it is regulated in laws and regulations, the enforcement of vaccination law is not easy to implement. This article aims to examine the formulation of the legal basis that can ensure effective enforcement of vaccination law in Indonesia. By using normative legal research, this study aims to answer several problems. First, is vaccination a right or obligation for every citizen? Second, what are the legal bases that can be used to enforce the vaccination law in Indonesia? Third, what is the state’s responsibility for adverse events following vaccination in return for the vaccination obligation? This article provides a view that the principle of emergency reason does not know the law (necessitas non habet legem) can be an indicator of a shift in vaccination status which was originally only a right to become obligation. In addition, the wederspanningheid article in the Criminal Code (KUHP) regarding resistance to officers carrying out state obligations can be the legal basis for enforcing vaccination law. Furthermore, the enforcement of vaccination law must also go hand in hand with the state’s responsibility for adverse events following vaccination. Responsibilities can be in the form of vaccine testing, treatment, care, and court lawsuits if there is a default or unlawful act.